Nonconvex ancient solutions to curve shortening flow - Zhang, Y; Olson, C; Khan, I; Angenent, S (American Mathematical Society, 2023)
We construct an ancient solution to planar curve shortening. The solution is at all times compact and embedded. For t ≪ 0 it is approximated by the rotating Yin-Yang soliton, truncated at a finite angle α(t) = −t, and closed off by a small copy of the Grim Reaper translating soliton.